Is pectoralis muscle index a risk factor for mortality in left ventricular assist device patients? - Erdoğan,Sevinç Bayer (2022)
SUMMARY OBJECTIVE: We aimed to investigate whether sarcopenia measured from pectoralis muscles is a risk factor for long-term mortality in left ventricular assist device patients. METHODS: Patients aged >18 years implanted with a left ventricular assist device in a single center between 2013 and 2019 were retrospectively included. Patients without a thoracic computed tomography scan performed within 3 months of left ventricular assist device implantation and without computed tomography scans appropriate for pectoralis muscle measurement were excluded. Pectoralis muscle measurements were made on thoracic computed tomography slices, and pectoralis muscle indices were calculated for each patient. Sarcopenia was defined as being in the gender-specific lowest tertile of pectoralis muscle index. Survival was compared between patients with and without sarcopenia. RESULTS: The study was conducted on 64 left ventricular assist device patients who met the inclusion criteria. Notably, 21 (32.8%) of the study patients were sarcopenic. Diabetes mellitus and sarcopenia were more common in patients with 2-year mortality in our cohort. Patients with sarcopenia had a worse 2-year survival (p<0.001). Sarcopenia had an adjusted hazard ratio of 4.04 (95% confidence interval (CI) 1.36–12.02, p=0.012), while diabetes mellitus was associated with an adjusted hazard ratio of 3.14 (95%CI 1.17–8.39, p=0.023). CONCLUSION: Sarcopenia defined by low pectoralis muscle index increases the risk for 2-year mortality in left ventricular assist device patients.